2022
DOI: 10.3390/nano12152572
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Doped Single-Walled Carbon Nanotubes as a New Adsorbent for Detecting and Trapping Volatile Organic Compounds: A First Principle Study

Abstract: Volatile organic compounds (VOCs) are in the vapor state in the atmosphere and are considered pollutants. Density functional theory (DFT) calculations with the wb97xd exchange correlation functional and the 6-311+G(d,p) basis set are carried out to explore the potential possibility of palladium-doped single-walled carbon nanotubes (Pd/SWCNT-V), serving as the resource for detecting and/or adsorbing acetonitrile (ACN), styrene (STY), and perchloroethylene (PCE) molecules as VOCs. The suggested adsorbent in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…1 that the addition of CNTs functionalized with amino groups declined the uptake of dichlorodiphenyldichloroethylene in lettuce roots from 78% to 23%. Furthermore, Yoosefian et al (2022) reported that Pd-CNTs have excellent adsorption characteristics for perchloroethene, suggesting this molecule as a potential adsorbent to detect and/or adsorb as VOCs in the atmosphere. On the other hand, graphene nanocomposites are considered other promising carbon nanomaterials for CVOCs removal.…”
Section: Adsorption By Nanoadsorbentsmentioning
confidence: 99%
“…1 that the addition of CNTs functionalized with amino groups declined the uptake of dichlorodiphenyldichloroethylene in lettuce roots from 78% to 23%. Furthermore, Yoosefian et al (2022) reported that Pd-CNTs have excellent adsorption characteristics for perchloroethene, suggesting this molecule as a potential adsorbent to detect and/or adsorb as VOCs in the atmosphere. On the other hand, graphene nanocomposites are considered other promising carbon nanomaterials for CVOCs removal.…”
Section: Adsorption By Nanoadsorbentsmentioning
confidence: 99%
“…Unfortunately, a considerable amount of the literature contains limited information regarding the properties of silver nanoparticles and the impact of synthesis conditions on them. [28] Among metallic nanocomposites, [29][30][31][32][33][34][35][36][37][38] silver nanoparticles are extensively studied and considered the most commonly used commercially due to their well-known antiviral properties. [39][40][41][42] Silver nanoparticles are known for their antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…They found that VOCs are adsorbed via a strong chemisorption process promoted by strong binding energies between the VOCs and the Pd-SWCNTs demonstrating that transition metal-loaded SWCNTs can be able to adsorb VOCs. 35…”
Section: Introductionmentioning
confidence: 99%
“…They found that VOCs are adsorbedvia a strong chemisorption process promoted by strong binding energies between the VOCs and the Pd-SWCNTs demonstrating that transition metal-loaded SWCNTs can be able to adsorb VOCs. 35 Recently, we reported the fabrication of novel carbon sponge materials based on functionalized and codoped carbon nanotubes. 20 The synthesized spongy carbon materials were functionalized with oxygen species such as hydroxyls and carboxyls.…”
Section: Introductionmentioning
confidence: 99%